The impact of psychological capital on green and organizational performance: Empirical research measuring psychological and subjective health of green building industries - Chen, Si-Xu; Tang, Yuan (Frontiers in Public Health, 2023)
Green building (GB) technologies have been introduced to reduce the negative effect of the building and construction industry on the economy, the ecosystem, and society. A more thorough and accurate knowledge of the factors for implementation is required to stimulate the wider adoption of GB technologies. The theoretical framework for this study is developed using psychological capital (PC), self-determination theory (SDT), and green theory. The study addresses gaps in the research in this field. The effect of PC on psychological health (PH), green innovation ambidexterity (GIA), and subjective health (SH), and the impact of GIA on green performance (GP) are determined. The effect of PH and SH on organizational performance (OP) is also determined. The information for this study is collected from a variety of sources in the Chinese GB industry. The subjects for this study are Chinese employees of GB-based companies. Using a convenience sampling method, a total of 504 employees were selected. The employees’ answers to a restricted, self-administered survey are used to generate the data. Data from this study shows that PC has a significant effect on GIA, SH, and PH and that GIA has a substantial impact on GP. Both SH and PH significantly affect OP. This study encourages managers in the green building industry to support fresh concepts in order to gain a competitive edge by implementing and promoting innovative cultures, especially in terms of service delivery and customer understanding, because innovation plays a critical role in these industries.